Does Participation in Digital Supply and Marketing Promote Smallholder Farmers’ Adoption of Green Agricultural Production Technologies? - Yuyang Li; Jiahui Li; Xinjie Li; Qian Lu (Land)
As global environmental challenges intensify, promoting green agricultural production technologies (GAPTs) that balance ecological and economic benefits at the farmer level has become a crucial pathway to achieving sustainable agricultural development. To achieve this goal, this study uses an Ordered Probit model, which empirically tests the impact and mechanisms of digital supply and marketing (DSM) participation on farmers’ adoption of GAPTs, based on a micro-survey of 1272 farmers from Shaanxi Province, Gansu Province, and the Ningxia Hui Autonomous Region in China. The findings reveal the following: (1) Participation in DSM effectively encourages farmers to adopt GAPTs. (2) Such participation enhances household per capita income, strengthens risk management, lowers entry barriers to high-value markets, and improves farmers’ access to information, thereby promoting the adoption of GAPTs. (3) Compared to low-capital, high-labor, and low-risk technologies, participation in DSM has a stronger incentivizing effect on the adoption of high-capital, low-labor, and high-risk technologies. This study offers novel empirical insights into the impact and mechanisms of DSM on farmers’ adoption of GAPTs. It provides micro-level evidence supporting the application of digital technologies in agriculture and safeguarding agricultural ecological sustainability.